2017
DOI: 10.1002/pc.24370
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale carbon fiber‐graphene oxide reinforcements for silicone resin composites with simultaneously enhanced interfacial strength and antihydrothermal aging behaviors

Abstract: Multiscale carbon fiber/graphene oxide (CF/GO) reinforcements were developed by chemically grafting GO onto the CF surface using tetraethylenepentamine (TEPA) as a bridging agent for methylphenylsilicone resin composites. Chemical structures and surface morphologies of CFs were systematically characterized. GO was uniformly grafted onto the surface of CFs by the formation of chemical bonding between CFs and GO. TEPA and GO grafting could enhance wettability, surface roughness and free energy significantly. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…This is because concentrated hydrochloric acid can oxidize and etch the surface of carbon fiber thereby increasing the O and N content 31 . After modification with KH550, Si elements appeared on the surface of CF and the content of N elements increased, which indicated that KH550 react with oxygen‐containing groups and successfully grafted the introduction of amino groups on the surface of CF 32,33 . In the curve of Figure 2, the peak of N increases again and the Si peak appears.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This is because concentrated hydrochloric acid can oxidize and etch the surface of carbon fiber thereby increasing the O and N content 31 . After modification with KH550, Si elements appeared on the surface of CF and the content of N elements increased, which indicated that KH550 react with oxygen‐containing groups and successfully grafted the introduction of amino groups on the surface of CF 32,33 . In the curve of Figure 2, the peak of N increases again and the Si peak appears.…”
Section: Resultsmentioning
confidence: 97%
“…31 After modification with KH550, Si elements appeared on the surface of CF and the content of N elements increased, which indicated that KH550 react with oxygencontaining groups and successfully grafted the introduction of amino groups on the surface of CF. 32,33 In the curve of Figure 2, the peak of N increases again and the Si peak appears. After modification by EVMG, the Si and N were reduced, this is because after KH550 modification, KH550 molecules accumulate on the surface and the outermost part of KH550 molecules in the fiber dissolves in the DMF solution.…”
Section: Surface Chemical Analysis By Xpsmentioning
confidence: 95%
“…Carbon nanomaterials, such as carbon nanotubes (CNTs) and graphene, had extensive application in the field of materials [13] on account of the nanotubes' modulus (1 TPa) and tensile strengths (150 GPa), [14][15][16][17] excellent chemical and physical properties of the thinnest material (graphene). [13,18,19] The rigid aromatic heterocyclic ring was a constitutional unit in polymer chain to obtain the high strength and high modulus materials .…”
Section: Introductionmentioning
confidence: 99%